Innovation in Human Resource Management to Create a Better Work Environment and Contribute to Organizational Success: A Systematic Literature Review - Akbar Hidayat, Wanda Gema Prasadio (Open Access Indonesia Journal of Social Sciences, 2023)
Amidst the digital revolution and industrial transformation, the human resource management paradigm has changed dramatically. Nowadays, innovation in HR is no longer just an option but a necessity for organizations that want to remain relevant and competitive. This change occurred because of the many challenges faced by companies in finding, developing, and retaining quality employees. The literature search process was carried out on various databases (PubMed, Web of Sciences, and Google Scholar) regarding the analysis of innovation in human resources management. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Innovation in human resource management (HR) has become the main driver for organizational transformation in facing the challenges and demands of the ever-evolving world of work. The use of advanced HRM information technology and software has helped increase efficiency in various aspects of human resource management, such as recruitment, training, development, and performance evaluation. Innovations in creating a work environment that balances work and personal life, as well as promoting equality and inclusion, have increased employee satisfaction and productivity.